2022
DOI: 10.1038/s42003-022-04190-2
|View full text |Cite
|
Sign up to set email alerts
|

Genomic ancestry, diet and microbiomes of Upper Palaeolithic hunter-gatherers from San Teodoro cave

Abstract: Recent improvements in the analysis of ancient biomolecules from human remains and associated dental calculus have provided new insights into the prehistoric diet and genetic diversity of our species. Here we present a multi-omics study, integrating metagenomic and proteomic analyses of dental calculus, and human ancient DNA analysis of the petrous bones of two post-Last Glacial Maximum (LGM) individuals from San Teodoro cave (Italy), to reconstruct their lifestyle and the post-LGM resettlement of Europe. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 70 publications
(104 reference statements)
0
20
0
Order By: Relevance
“…Interestingly, diseased modern samples were characterized by increased Gram-negative, anaerobic bacteria. The ancient samples exhibited similar characteristics, hinting at the possibility of dental disease for those ancient individuals [147]. These findings are contradicted by Velsko et al [141], who found that there were no patterns linking a state of dental disease with changes in the composition or function of the oral microbiomes of smokers and non-smokers in post-Medieval Netherlands.…”
Section: Diseasementioning
confidence: 80%
“…Interestingly, diseased modern samples were characterized by increased Gram-negative, anaerobic bacteria. The ancient samples exhibited similar characteristics, hinting at the possibility of dental disease for those ancient individuals [147]. These findings are contradicted by Velsko et al [141], who found that there were no patterns linking a state of dental disease with changes in the composition or function of the oral microbiomes of smokers and non-smokers in post-Medieval Netherlands.…”
Section: Diseasementioning
confidence: 80%
“…After perusing the full-text versions, 19 articles were selected for the purpose of framing the scoping review (Table 1). They were published between 2013 and 2023 [7,21,22,24,[37][38][39][40][41][42][43][44][45][46][47][48][49][50]. No data emerged about the age of the ancient population sampled, except for one study reporting data on a juvenile mandible [47], and others clarified that the ancient population was of adult age [46,49].…”
Section: Resultsmentioning
confidence: 99%
“…A study does not specify the samples' geographical origin [40]. The human remains herein taken into account range from 6000 years ago to the 19th century [7,21,22,24,26,[37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Geographical Origin and Historical Dating Of Dental Calculus...mentioning
confidence: 99%
“…Four microliters of the sample/control were injected. LC and MS parameters were run according to the dental calculus method in Scorrano et al 102 , with the HCD collision energy at 30%, RF Lens at 40%, and MS2 inject time of 54 ms to adjust for differences between the mass spectrometers.…”
Section: Methodsmentioning
confidence: 99%